2018
DOI: 10.1055/s-0038-1668522
|View full text |Cite
|
Sign up to set email alerts
|

Risk Score for Prediction of 10-Year Atrial Fibrillation: A Community-Based Study

Abstract: We provide a simple score for the prediction of 10-year risk for AF. The score can be used to select patients at highest risk for treatments of modifiable risk factors, monitoring for sub-clinical AF detection or for clinical trials of primary prevention of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
68
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 41 publications
2
68
0
4
Order By: Relevance
“…After consolidating all the publications, a total of 3466 records were obtained (Figure 1). After eliminating duplicates, the figure fell to 3132 and of these, 3114 were excluded, since neither the title nor the abstract indicated that the publication described a predictive model of the characteristics proposed, leaving 18 articles to be analyzed in full text 16‐33 . Analysis of these articles resulted in 12 more publications being excluded, 16‐27 five because they were congress abstracts, 16‐20 two because they were revisions, 21,22 two because the authors analyzed the predictive value of risk factors, 23,24 two because the models were not performed in the general population, 25,26 and one because the authors did not use their own data 27 .…”
Section: Application To a Real Case: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After consolidating all the publications, a total of 3466 records were obtained (Figure 1). After eliminating duplicates, the figure fell to 3132 and of these, 3114 were excluded, since neither the title nor the abstract indicated that the publication described a predictive model of the characteristics proposed, leaving 18 articles to be analyzed in full text 16‐33 . Analysis of these articles resulted in 12 more publications being excluded, 16‐27 five because they were congress abstracts, 16‐20 two because they were revisions, 21,22 two because the authors analyzed the predictive value of risk factors, 23,24 two because the models were not performed in the general population, 25,26 and one because the authors did not use their own data 27 .…”
Section: Application To a Real Case: Resultsmentioning
confidence: 99%
“…Analysis of these articles resulted in 12 more publications being excluded, 16‐27 five because they were congress abstracts, 16‐20 two because they were revisions, 21,22 two because the authors analyzed the predictive value of risk factors, 23,24 two because the models were not performed in the general population, 25,26 and one because the authors did not use their own data 27 . Accordingly, six scientific articles that followed the 11 CHARMS domains were finally analyzed 28‐33 . The following acronyms are used to facilitate the nomenclature of the three older articles: ARIC (atherosclerosis risk in communities), 32 CHARGE‐AF (cohorts for heart and aging research in genomic epidemiology‐atrial fibrillation), 31 and FHS (Framingham heart study) 33 …”
Section: Application To a Real Case: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Several recognized risk factors for atrial fibrillation were previously identified, including advanced age, male sex, hypertension, diabetes mellitus, coronary artery disease, heart failure, sleep apnea, sedentary lifestyle, smoking and obesity. 6,7 Recent risk scores predicting atrial fibrillation development have been proposed, 8,9 showing moderate discriminatory power (C-statistic 0.75). Notably, these risk scores were based entirely on clinical data, to the exclusion of social and environmental determinants.…”
mentioning
confidence: 99%